Prevention - Essers S; Schöffl V; 4; Heggie TW; Küpper T; 4 (Dynamic Media Sales Verlag, 2019)
Objective: The objective of this study was to investigate whether the actual First Aid (FA) knowledge of German physical education (PE) teachers in 2014 differed from a 2008 pilot study (PS) that revealed a lack of FA knowledge amongst German PE teachers. Additionally, a second objective was to identify whether or not the current FA knowledge is at an appropriate level to handle school sport injury incidents.Material and methods: A multiple-choice questionnaire was compiled based on a questionnaire of the PS and on actual analysis of school sport accidents in Germany. It was answered by secondary school PE teachers (n=92). The results were compared to the results of the pilot studyin2008 using non-parametric tests. Results: A general lack in FA knowledge was identified as only two of 54 statements were answered correctly by all participants, especially in basic topics such as positioning, limb fractures, back injuries and the effects of climatic influence like heat and cold.Conclusions: In order to improve PE teachers FA knowledge and adapt it to the school sport accidents they face, it is recommended that PE teachers participate in sports-specific FAtraining and refresher courses every two years and that this training bepart of their academic education and postgraduate training.KEY WORDS: Physical Education, Accidents, First Aid